Implementasi Aplikasi Berbasis Website Rental Kendaraan Berbasis PHP & MYSQL - Riyan Nugraha; Rudi Nurwanto; Erwantoro (Elkom : Jurnal Elektronika dan Komputer, 2022)
Information technology is a very important means ofinformation for a company. Information is expectedto facilitate work or activities to achieve goalsoptimally. With the increasing popularity of theinternet, many business fields, especially large-scaleones, have provided online services, but this is notthe case for small and medium-sized businesses suchas the car rental business, by utilizing web servicesthat contain information and ordering applications, itis hoped that they will become promotional mediaand will expedite the ordering process. The researchmethod used in building a rental car bookingapplication with web services is by means of needsanalysis, system design, database design, and screendialog design.